Invisible migrant enclaves in Chinese cities: Underground living in Beijing, China. (November 2015) - Huang, Youqin; Yi, Chengdong
China is experiencing an urban revolution, powered in part by hundreds of millions of migrant workers. Faced with institutionalised discrimination in the housing system and the lack of housing affordability, migrants have turned to virtually uninhabitable spaces such as basements and civil air defence shelters for housing. With hundreds of thousands of people living in crowded and dark basements, an invisible migrant enclave exists underneath the modern city of Beijing. We argue that in Chinese cities, housing has been adopted as an institution to exclude and marginalise migrants, through: (a) defining migrants as an inferior social class through the Hukou system and denying their rights to entitlements including housing; (b) abnormalising migrants through various derogatory naming and categorisations to legitimise exclusion; and (c) purifying and controlling migrant spaces to achieve exclusion and marginalisation. The forced popularity of basement renting reflects the reality that housing has become an institution of exclusion and marginalisation. It embodies vertical spatial marginalisation, with exacerbated contrasts between basement tenants and urban residents, heightened fear of the 'other', even more derogatory naming, and the government's more aggressive clean-up of their spaces. We call for reforms and policy changes to ensure decent and affordable housing for basement tenants and migrants in general.